ADAPTASI KRITIS CINDERELLA: PENDEKATAN NARATOLOGI GÉRARD GENETTE BAGI PENDIDIKAN LITERASI ANAK - Meina Febriani; Sri Sumaryani; Diyamon Prasandha (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
The Brothers Grimm's Cinderella is a world classic that contains gender bias and patriarchal ideology, which require critical examination. This study aimed to analyse the narrative structure of Cinderella through Gérard Genette's narratological theory and to formulate a critical adaptation model based on Jack Zipes' framework. The study employed a qualitative approach using Genette's narratological theoretical framework, consisting of five categories: order, duration, frequency, mood, and voice. The data analysis consisted of five stages: narrative mapping, structural analysis, ideological critique, critical adaptation, and pedagogical interpretation. The results suggest that the narrative features a progressive, linear plot and minimal temporal distortion, dynamic duration variation, diverse narrative frequencies, a didactic mood with dominant external focalization, and a heterodiegetic voice that emphasizes the moral and structural functions of the story. Comparatively, the Grimm's version presents passive characters, while the critical adaptation reconstructs active female agency, equal relationships, and the elimination of symbolic violence. The conclusion confirms that integrating the two approaches yields a transformative model for developing reading materials grounded in critical literacy and gender equality.